Effect of valproic acid on overall survival in patients with high-grade gliomas undergoing temozolomide: A nationwide population-based cohort study in Taiwan. Issue 28 (10th July 2020) - Kuo, Yu-Jen; Yang, Yao-Hsu; Lee, I-Yun; Chen, Pau-Chung; Yang, Jen-Tsung; Wang, Ting-Chung; Lin, Martin Hsiu-Chu; Yang, Wei-Hsun; Cheng, Chun-Yu; Chen, Kuo-Tai; Huang, Wei-Chao; Lee, Ming-Hsueh
Abstract : Abstract: High-grade gliomas (HGGs) are a rapidly progressive and highly recurrent group of primary brain tumors. Despite aggressive surgical resection with chemoradiotherapy, prognoses remained poor. Valproic acid (VPA), a histone deacetylase inhibitor has shown the potential to inhibit glioma cell growth in vitro through several diverse mechanisms. However clinical studies regarding the effect of VPA on HGGs are limited. This study aimed to investigate whether using VPA in patients with HGGs under temozolomide (TMZ) would lead to a better overall survival (OS). We used the Taiwan National Health Insurance Research database to conduct this population-based cohort study. A total of 2379 patients with HGGs under TMZ treatment were included and were further classified into VPA (n = 1212, VPA ≥ 84 defined daily dose [DDD]) and non-VPA (n = 1167, VPA < 84 DDD) groups. Each patient was followed from 1998 to 2013 or until death. A Cox proportional hazard regression was performed to evaluate the effect of VPA and OS. The VPA group had a longer mean OS time compared with the non-VPA group (OS: 50.3 ± 41.0 vs 42.0 ± 37.2 months, P < .001). In patients between 18 and 40 years old, the difference is most significant (OS: 70.5 ± 48.7 vs 55.1 ± 46.0, P = .001). The adjusted hazard ratio is 0.81 (95% confidence interval, 0.72–0.91) for the VPA group relative to the non-VPA group. VPA at over 84 DDD improved OS in HGGs TMZ treatment.